Antagonistic Interaction of Selenium and Cadmium in Human Hepatic Cells Through Selenoproteins - Ramírez-Acosta, S.; Uhlírová, R.; Navarro, F.; Gómez-Ariza, J. L.; García-Barrera, T. (Frontiers in Chemistry, 2022)
Cadmium (Cd) is a highly toxic heavy metal for humans and animals, which is associated with acute hepatotoxicity. Selenium (Se) confers protection against Cd-induced toxicity in cells, diminishing the levels of ROS and increasing the activity of antioxidant selenoproteins such as glutathione peroxidase (GPx). The aim of this study is to evaluate the antagonistic effect of selenomethionine (SeMet) against Cd toxicity in HepG2 cells, through the modulation of selenoproteins. To this end, the cells were cultured in the presence of 100 µM SeMet, 5 µM, 15 µM and 25 µM CdCl2 and a combination of both species for 24 h. At the end of the experiment, cell viability was determined by MTT assay. The total metal content of Cd and Se was analyzed by inductively triple quadrupole coupled plasma mass spectrometry (ICP-QqQ-MS). To quantify the concentration of three selenoproteins (GPx, selenoproteins P (SELENOP) and selenoalbumin (SeAlb)) and selenometabolites an analytical methodology based on column switching and species unspecific isotopic dilution approach using two-dimensional size exclusion and affinity chromatography coupled to ICP-QqQ-MS was applied. The co-exposure of SeMet and Cd in cells HepG2 enhanced the cell viability and diminished the Cd accumulation in cells. Se supplementation increased the levels of selenometabolites, GPx, SELENOP and SeAlb, however the presence of Cd resulted in a significant diminution of selenometabolites and SELENOP. These results suggest that SeMet may affects to the accumulation of Cd in cells, as well as a suppression of selenoprotein synthesis induced by Cd.